Peran Keluarga dalam Meningkatkan Kesadaran Tentang Kesehatan Mental - Novia Lisma Nanda (Journal Innovation In Education, 2025)
Mental health is an important element in individual well-being that is often overlooked. The family as the smallest social unit plays a significant role in raising awareness of mental health among its members. This article aims to explore the role of the family in supporting mental health by involving good communication strong emotional support and positive parenting. This study uses a literature review method to analyze various studies relevant to the topic. Findings from various sources indicate that active family involvement can play a key role in preventing and overcoming mental health disorders. Open communication between family members facilitates sharing of feelings and problems so that individuals feel more comfortable expressing their feelings without fear of being punished or judged. Emotional support from the family such as affection attention and empathy, has been shown to be effective in reducing feelings of stress and anxiety that can lead to mental disorders. In addition, healthy parenting such as a democratic approach that provides freedom while still providing direction also contributes to children's mental health. Based on these findings this article suggests the importance of increasing mental health literacy at the family level. With better knowledge families can provide appropriate support create a more supportive environment and play an active role in maintaining the mental health of their family members.